You are on page 1of 21

# The Algebra Toolbox

Part Three Subject Changing (aka Transposition) Simultaneous Equations

The Algebra Toolbox
Contents Section
1. Changing the Subject 2. Simultaneous Equations

Topics
a. Introduction b. Examples a. Introduction b. Substitution method c. Elimination method

Page
3 4 12 13 16

1. CHANGING the SUBJECT
Often we need to rewrite an equation in a different format. For example, the equation x+y=4 may need to be rewritten so that there is one letter on its own on the left. This means we have to cut ‘n’ paste! Let’s get “y” alone on the left, by cut ‘n’ pasting the “x” to the right. Before we do, remember the equation is really +x + y = 4 Now cut ‘n’ paste, remembering to switch the “+ x” to “ – x” y=4–x We could have put the “– x” in front of the 4, and written it as y=–x+4 So either y = 4 – x, or y = – x + 4 would have done. This is called “Making y the subject”

In the example above, x+y=4 we might have needed to get “x =” rather than “y =”. The method is still the same! This time cut ‘n’ paste the “y” to the other side: x = 4 – y or x = – y + 4 is the answer!! This is called “Making x the subject”

3

Example 1 Make b the subject of a+b=c
Realising we want “b” alone, we need to get rid of the “a”. Cut ‘n’ paste “a” to the right:

+a + b = c becomes b = c – a …ANSWER!! Example 2 Make y the subject of a+x–y=6
METHOD 1 Cut’n’ paste the y to the right, and the 6 to the left: METHOD 2 Cut ‘n’ paste the “a” and “x” to the right:

a+x–y=6 a+x–6=y
Swap left & right sides (no sign changes)

a+x–y=6 –y=6–a–x
Now we must have just “y”, we can’t have “ – y” so we need to change all the signs:

y = a + x – 6 …ANSWER !!

– y = 6 – a – x becomes +y = – 6 + a + x y = – 6 + a + x…ANS!!

Can you see what was behind Method 1? Getting the – y across to the right got rid of the minus sign in front, and made it just “y”. This is a smart move! Minuses can be a pain!

4

Example 3 Make p the subject of 2p + y = 3x
To get “p” alone, there are two things we have to get rid of….the “y” and the “2”. Remember we can get rid of the y by cut ‘n’ paste (because it’s connected by a + sign) 2 by dividing! (because it’s connected by a × sign) Always do cut ‘n’ paste first:

2p + y = 3x 2p = 3x – y

becomes

Now get rid of the 2 by dividing all three terms by 2:

2 p 3x y = − 2 2 2
The reason for doing this division by 2 is so the 2’s will cancel and leave you with just “p” !!

2 p 3x y = − 2 2 2 p= 3x y − …ANSWER!! 2 2 3x − y !! 2

OR….you could also have written it as p =

5

Example 4 Make “a” the subject of 2ab – y =
3x 2

Get rid of any fractions first – before you do anything else. Remember what to do? There are 3 terms. There’s a 2 in the bottom of the fraction. Multiply everything through by 2 !!

Remember

4ab – 2y = 3x
Now we have to get rid of the:

3x × 2 = 3x !! 2

2y (use cut ‘n’ paste because this is connected by a “ – “ sign) the 4 and the b (use division because these are connected by a “×” sign) Cut ‘n’ pasting the 2y to the right:

4ab – 2y 4ab

= 3x becomes: = 3x + 2y

Dividing by 4b

a =

3x + 2 y ….ANSWER 4b

Could also have written a =

3x 2 y 3x y which equals + + 4b 4b 4b 2b

6

Example 5 Make t the subject of
5w − pt = 2y x
Can you remember the first step? If you said “Get rid of the fraction first” you’d be right!! There are 2 terms, and an “x” is in the bottom. Multiply both sides by x.

5w − pt × x = x

2y × x

Cancelling the x’s on the left

5w – pt

= 2xy
Remember we’re interested in the “t”. It has a minus in front. Do you remember our smart trick from before, where we move it across to the right to get rid of the minus?

5w – 2xy

= pt
All that now remains is the p to get rid of. Remember because the p is connected to the t by multiplication, we must divide. Divide all 3 terms by p:

5w − 2 xy = t ….ANSWER! p

7

Example 6 Make u the subject of
a =y u
First step? Yep. Get rid of the fraction first !! There are 2 terms, and a “u” is in the bottom. Multiply both sides by u.

a × u = y× u u
Cancelling the u’s on the left,

a

= yu
Remembering we want u alone, we divide both sides by y, because y is connected to u by multiplication.

a y

=

yu y

Cancel the y’s on the right:

a y a y

=

yu y

8

Example 7 Make p the subject of t – 3p = x(4 + yp)
First step is to get rid of the brackets!!
BEWARE!!! The term we want to isolate, the p, APPEARS TWICE!! In your answer, you can only have the p appearing once, so special care is needed!!

t – 3p = x × 4 + x × yp t – 3p = 4x + pxy
Now we cut ‘n’ paste trying to get the p terms together on one side. Let’s move the p’s to the right (Why??) and the non-p’s (t and 4x) to the left.

t – 3p = 4x + pxy t – 4x = pxy + 3p
Once the p’s are together on the right, we factorise. This brings the p out the front, and means we now have only one p present!

t – 4x = p(xy + 3)
We now need to get rid of the (xy + 3). This is connected to p by multiplication, so what do we do??? DIVIDE both sides by (xy + 3) !!

t − 4x p ( xy + 3) = ( xy + 3) ( xy + 3)
Cancel the (xy + 3) on the right!

t − 4x = p ….ANSWER!! ( xy + 3)

Note…Right back at the start, had you taken the p terms to the left rather than the right side, you would have ended up with – 3p – pxy = 4x – t p(– 3– xy) = 4x – t p=

4x − t − 3 − xy

THIS IS EXACTLY THE SAME AS THE ANSWER AT LEFT

9

Example 8 Make y the subject
4 xy = 2 pw 3 − ay

First get rid of the fraction. Multiply both sides by (3 – ay)

4 xy × (3 – ay) 3 − ay

=

2pw × (3 – ay)

Cancel the (3 – ay) on the left Expand the right to get rid of the brackets

4xy = 6pw – 2apwy
Again we have the “y” occurring twice. Remember what to do? Move the y’s to one side. LEFT side is best this time. (means the y’s won’t have minuses)

4xy + 2apwy = 6pw
Factorise the left. Remember this means the y will only appear once (we want this to happen)

y(4x + 2apw) = 6pw
Divide both sides by (4x + 2apw)

y (4 x + 2apw) 6 pw = (4 x + 2apw) (4 x + 2apw)
Now cancel the (4x + 2apw) on the left:

y (4 x + 2apw) 6 pw = (4 x + 2apw) (4 x + 2apw) y= 6 pw …ANSWER!!! (4 x + 2apw)

10

Practice Exercises 1
Make the bracketed letter the subject xz − y 1. a – b = c [a] 9. =4
a

[x] [a], [b] [w]

2. 2w + c = d 3. 3a + bd = y 4. 2x + y = ax + c
x =b−6 a x −t = c a 2x − 3 =v a

[w] [d] [x]

10. a – b = 2x 11. w – kw = x + pw
a =k b − tx

12.

[x]

5. 6. 7.

[x] [x] [x] [v]

8. x − = p

u v

11

2. SIMULTANEOUS EQUATIONS
(a) INTRODUCTION
Sometimes you will have a pair of equations containing two variables (like “a” and “b”), and be asked to find the values of the letters that make the equations true. For example, the equations a+b=7 2b – a = 5 are both satisfied when a = 3 and b = 4. In fact, a = 3 and b = 4 are the only answers that fit both these equations!
You will note that a = 5, b = 2 certainly fits the first equation, but when we feed these numbers into the second equation, it becomes 2×2 – 5 = 5, which of course is not true! So, a = 5, b = 2 is no good (not a solution) because it fits only one of the equations. You can find heaps of numbers like a = 5, b = 2 which will fit only one of the equations, but they’re useless! We’re only interested in the numbers that fit both equations, and they are of course, a = 3 and b = 4.

So, we say that a = 3 and b = 4 are the solutions to the simultaneous equations a + b = 7; 2b – a = 5. There are two good methods to solving simultaneous equations. The first is called substitution. The second is called elimination.

12

(b) SOLVING SIMULTANEOUS EQUATIONS BY SUBSTITUTION
This is best learned by examples. Example 1 Solve a+b=7 2b – a = 5
(These are the ones from the previous page!)
Equation (1) Equation (2)

Method:
Find a “lone letter” – a letter without a number multiplying it. There are 3 of these here (the “a” and “b” in the 1st equation, and the “a” in the 2nd equation). Make one of these the subject of its equation. Let’s pick the “a” in the top equation:

a+b=7
Use cut’n’paste to get “a” on its own:

a=7–b

Now substitute this into the 2nd equation:

2b – a = 5 now becomes 2b – (7 – b) = 5

When substituting something with 2 terms like 7 – b, it’s smart to put it in brackets! You’ll see why below.

This is now an equation with only one letter! We can solve it!! (See Toolbox 1 if you’ve forgotten!)

2b – (7 – b) 2b – 7 + b 3b – 7 3b b=4

=5 =5 =5 = 12

Remember the sign change??

We have b. Now we need to find “a”. We know b is 4, so replace b with 4 in either Equation (1) or (2). Equation 1 (the simpler!) becomes a + 4 = 7, and so a=3 Final answer is a = 3, b = 4 !! 13

Example 2 Solve 2x – 3y = 19 5x + y = 22 Method:
Find the “lone letter” – a letter without a number multiplying it. There is only one of these here (the “y” in the 2nd equation). Make y the subject of Equation 2.
Equation (1) Equation (2)

5x + y = 22
Use cut’n’paste to get “y” on its own:

y

Now substitute this into the 1st equation:

= 22 – 5x

2x – 3y = 19 now becomes 2x – 3(22 – 5x) = 19
Now we have only one letter!

Why do you think we put the 22 – 5x in brackets? Because if we don’t, we could overlook the sign change (below in blue).

2x – 3(22 – 5x) = 19 2x – 66 + 15x = 19 17x – 66 = 19 17x = 85 x=5

Remember the sign change??

We have x. Now we need to find “y”. We know x is 5, so replace x with 5 in either Equation (1) or (2). Equation 2 (the simpler!) becomes 5 × 5 + y = 22 25 + y = 22 y= –3 Final answer is x = 5, y = – 3 !!

14

Example 3 Solve 3a + 2b = 15 5a + 4b = 26 Method:
This time there’s no “lone letter” so go for the letter with the smallest coefficient (multiplying number in front). The “b” in the 1st equation is the best bet. Make b the subject of Equation 1.
Equation (1) Equation (2)

3a + 2b = 15
Use cut’n’paste to get rid of the 3a:

2b b

= 15 – 3a
Now divide through by 2

=

15 3a − 2 2

Now substitute this into Equation 2:

5a + 4b = 26 now becomes 5a + 4(
15 3a − ) = 26 2 2
Expand the brackets & cancel the fractions

4(

5a + 30 – 6a = 26 30 – a –a –a a a=4 = 26 = 26 – 30 = –4 = 4

= 2 × 15 = 30 – 6a

15 3a − ) 2 2 15 3a =4× –4× 2 2

– 2 × 3a

We have a. Now we need to find “b”. We know a is 4, so replace a with 4 in either Equation (1) or (2). Equation 1 becomes 3 × 4 + 2b = 15 12 + 2b = 15 2b = 15 – 12 2b = 3 b =1½ Final answer is a = 4, b = 1 ½ !! 15

(c) SOLVING SIMULTANEOUS EQUATIONS BY ELIMINATION
This method is an alternative to substitution. It is a good method to use when there is no letter “on its own”, e.g. like in the previous Example 3, where all 4 letters had numbers attached to them. Example 4 Solve (by elimination) 3a + 2b = 15 5a – 4b = 14
Equation (1) Equation (2)

The trick here is to make the numbers in front of one of the letters match, and have opposite signs. Watch what happens: We are going to double Equation 1 right through:

6a + 4b = 30 5a – 4b = 14

Equation (3) Equation (2)

What do you notice about these 2 equations? The key: the numbers in front of “b” are now the same, with opposite signs. This is what we want to try to aim for!
Once we have done this, we now work with the “new” equations, Equation (3) and Equation (2).

11a + 0 = 44 11a = 44 a=4

Getting zero means we’ve eliminated b!!

Now feed a = 4 into any of the Equations (1), (2) or (3) to find b. (I’ll choose Equation (1) because the “b” has a 2 in front of it (smaller is easier!)

3a + 2b = 15 3 × 4 + 2b = 15 12 + 2b = 15 2b =3 b = 1 ½ ……..Final answer a = 4 and b = 1 ½ 16

Example 5 Solve (by elimination) 2a + 3b = 9 3a + 4b = 11
Equation (1) Equation (2)

We want make the numbers in front of one of the letters match, and have opposite signs. Let’s choose the “a” terms, because their numbers are smaller overall than those in front of the “b”s.
The a’s have a “2” and a “3” in front. How can I make them the same number?

2a + 3b = 9 3a + 4b = 11

We can turn a “2” and a “3” both into a 6 easily (2 and 3 can be multiplied to make 6)

2a + 3b = 9 3a + 4b = 11

Multiply this through by 3 Multiply this through by 2

6a + 9b = 27 6a + 8b = 22

What do you notice about these 2 equations? The numbers in front of “a” are now the same, but we need opposite signs (so the numbers will cancel when we add). So change all the signs in one of the equations (doesn’t matter which one).

6a + 9b – 6a – 8b

= 27 = – 22
9b + – 8b = 9b – 8b = 1b 27 + – 22 = 27 – 22 = +5

0+b b

=5 =5 =9 =9 = 9 – 15 = –6 = – 3 …..FINAL ANSWER a = – 3 , b = 5

Now feed b = 5 into Equation (1) up the top:

2a + 3b 2a + 15 2a 2a a 17

Example 6 Solve the equations 9+x=y x + 2y = 12 by both methods Substitution
Make “x” the subject of Equation (1)
Equation (1) Equation (2)

Elimination
Rearrange the equations so the x’s, y’s and numbers (the 9 and the 12) are aligned vertically:

x=y–9
Substitute this into Equation (2)

x–y= –9 x + 2y = 12
(Did you follow how the top equation came about? the 9 and the y were cut ‘n’ pasted) Now noticing the x’s both already match (number in front of each is 1), all we have to do is a sign swap on one of the equations. Let’s change all signs in Eq (1):

x + 2y = 12 becomes (y – 9) + 2y = 12
Tidy up by collecting y terms

3y – 9 = 12 3y = 21 y=7
Substitute y = 7 into Equation 1 (or 2)

–x+y= 9 x + 2y = 12

9 + x = y becomes 9+x=7 x=7–9 x= –2 Final answer x = – 2, y = 7

0 + 3y = 21 3y = 21 y=7
Feed this into either equation up top

9+x=y 9+x=7 x=7–9 x= –2 Final answer x = – 2, y = 7

18

So how do I know which method to use? The general rule is: If there is a letter on its own, then it’s usually easiest to make that letter the subject and use substitution, as in Examples 1, 2 and 3. If there’s no letter on its own, then elimination is usually the best method, as in Examples 4 and 5. Sometimes you’ll have a choice, in which case it’s best to use the method you’re most comfortable with!!

Practice Exercises 2
Solve these pairs of simultaneous equations. Use either method. 1 2 3 4 5 6 7 8 x+y=8 x–y=2 x–y=2 2y = x + 1 3 = 2x + y 4x + 6 = 10y x–y=2 3x + y = 10 2x – y = 6 3x + y = 14 x+y=5 4x + y = 14 2x + 3y = 23 x + 3y = 22 c + 2d = 6 9c + 2d = 54 9
Remember to rearrange! See Ex 6 Remember to rearrange! See Ex 6

10 11 12 13 14 15 16

x+y=6 x–y=1 3x – 5y = 13 2x + 5y = – 8 y=x–2 Remember to rearrange! See Ex 6 x = 2y – 1 Remember to y=6–x rearrange! See Ex 6 2x + y = 8 10x + 3y = 12 3x + 5y = 20 3x + 4y = 15 3x + 2y = 12 2x + 3y = – 8 2x + y = – 4 3a – 5b = – 3 4a – 5b = 1

19

Changing the subject of an equation – A quick example
This means that you identify a specific letter you want to get alone on one side of the “=” sign. You then use cut ‘n’ paste to remove everything else from that side, leaving the letter alone. e.g. if we wanted to make “y” the subject of the equation 2y – x = 7, we have to remove the x and the 2 from the left side, which will then leave us with x as the subject. 2y – x = 7 2y =x+7
y

cut ‘n’ paste the – x from the left to the right (becomes + x) divide all 3 terms by 2

=

x 7 + 2 2

20

ANSWERS Exercise 1 (1) a = b + c (2) w =

d −c y − 3a c− y (3) d = (4) x = (5) x = ab – 6a (6) x = ac + at 2 b 2−a

(7) x =

u 4a + y av + 3 (8) v = (9) x = (10) a = b+2x; b = a – 2x 2 x− p z x bk − a a − bk (11) w = (12) x = or x = 1− k − p kt − kt

ANSWERS Exercise 2 (in alphabetical order x first, then y) (1) 5 & 3 (7) 1 & 7 (13) 0 & 4 (2) 5 & 3 (8) 6 & 0 (14) 3 & 1 ½ (3) 1 & 1 (4) 3 & 1 (9) 3 ½ & 2 ½ (10) 1 & – 2 (15) – 1 & – 2 (16) 4 & 3 (5) 4 & 2 (11) 5 & 3 (6) 3 & 2 (12) 2 & 4

21